ANALYSIS OF THE RATIONALITY OF ANTIPLATELET USE IN ISCHEMIC STROKE PATIENTS AT “X” HOSPITAL, SEMARANG CITY - Wibowo, Sulistiyanto; Dian A, Yustisia; Hasanah A.M, Restu (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Ischemic stroke accounts for approximately 85% of all stroke cases and remains a major global health problem. Antiplatelet agents are key for secondary prevention, but irrational use may reduce effectiveness and increase bleeding risk. This retrospective descriptive study evaluated the rationality of antiplatelet use in ischemic stroke patients at “X” Hospital, Semarang City, from January to July 2024. Patients aged ≥26 years with complete medical records were included. Rationality was assessed based on PNPK Stroke Guidelines (2019), AHA/ASA Guidelines (2021), and AHFS Drug Information (2024) using three indicators: appropriate drug, dose, and patient. A total of 111 patients (113 cases) met the inclusion criteria. Most were male (58.56%) and aged >65 years (36.04%), with hypertension, diabetes, and hyperlipidemia as common comorbidities. Aspirin was the most used monotherapy (38.05%), and aspirin–clopidogrel the most frequent combination (37.17%). Drug selection accuracy was high (96.46%), while dose accuracy was low (44.25%). Antiplatelet use at “X” Hospital demonstrated rational drug selection but suboptimal dosing. Improved adherence to dosing guidelines and periodic prescription review are needed to enhance patient safety and treatment outcomes.